Design and Build a Seminar Management Information System to Manage 2019 Indonesian Qualitative Seminar & Workshop (SLKI) - Simon Prananta Barus (International Journal of Informatics and Computation, 2020)
Matana University collaborated with Indonesia Qualitative Researcher Association (IQRA) held a 2019 Indonesian Qualitative Seminar & Workshop (SLKI) 2019. The organizer required a seminar management information system (SIM) to run this event smoothly. However, seminar SIM was not available at that time, and needed to be built according to the needs of 2019 SLKI. The methodology to build seminar SIM is study literature system development with prototyping model which has the stages of user requirement, system / sub system prototyping, prototype evaluation, prototype improvement, system testing, system implementation, system maintenance. SIM 2019 SLKI consists of 2 (two) main applications, namely a web-based data management application and mobile based attendance application. QR Code was used for the attendance of participants. This seminar SIM successfully has been built and implemented in this event. This seminar SIM helped the participants and the committee to share data and information that can be done anytime and anywhere as long they are connected to the internet. In the future, it is necessary to develop several features such as article management, QR code generator, automatic certificate generation, digital payment, and more complete reporting & webinar implementation.